THE EFFECT OF TELEVISION MEDIA TOWARDS ATTITUDE STUDENTS LEARN ON CIVIC EDUCATION LEARNING IN JUNIOR HIGH SCHOOL DISTRICT OF PANGEAN REGENCY KUANTAN SINGINGI - Kokom Komalasari, Ilham Hudi Aim Abdulkarim (Jurnal Civicus, 2015)
This study used a survey method with quantitative approach, by developing two independent variables (the television media), and one dependent variable (attitude of students in learning civics). This research was conducted in SMP-MTS Se-District of Pangean Regency Kuantan Singingi. The subjects of the study were the students of SMP-MTS Se-District of Pangean Class VIII with all class VIII student population of 220 students with a sample of 140 students. To determine the number of samples the author uses two stages: looking for a sample of the total population using multistage random sampling technique. The collection of primary data in this study using a questionnaire containing statements with five alternative answers (Likert scale). Research findings: (1) there is influence between the variables TV media with the type of education (X1) on the attitudes of students in the learning PKN (Y) with a score of 30.3%. (2) there are significant variables with this type of entertainment TV media (X2) on the attitudes of students in the learning PKN (Y) with a score of 27.4%. (3) there is the influence of TV media (X) on the attitudes of students in the learning PKN (Y) with a score of 30.4%.Keyword : Television, Learning Attitude, Civic Education.